Experimental and Numerical Studies on Rock Cutting with Saw Blade and Conical Pick Combined Cutting Method. (30th October 2019) - Lu, Zhenguo; Zeng, Qingliang; Wang, Zhiwen; Li, Xu; Gao, Kuidong
Abstract : In the rock cutting process, conical pick wear is often encountered. In order to restrain this condition, a saw blades and conical pick combined cutting method was put forward. Saw blades were employed to slit the rock for increasing the free surface, and then the conical pick was used to break the rock. To research the cutting performance of the new cutting method, the corresponding experimental device and a three-dimensional finite element model are established. In order to obtain crack propagation and fragment separation and to study the fracture process of the rock plate, a damage constative model and failure mechanism were combined in the numerical model. The mechanical tests were carried out to achieve the mechanical parameters of the rock. To investigate different parameters affecting rock plate cutting performance, experiments with different compressive strengths, physical parameters, and cutting depths were carried out. Moreover, the confining pressures affecting the cutting performance were adopted to simulate deep mining conditions. The experimental results demonstrated that the peak cutting force shows the exponential positive correlation with compressive strength, thickness of the rock plate, and cutting depth of the conical pick, and exhibits the exponential positive correlation with rock plate height and width. Besides, the numerical simulation results show that peak cutting force and confining pressure have a binomial relationship.